2007
DOI: 10.1152/physiol.00015.2007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Altered Calcium Physiology in the Heart: Translational Approaches to Excitation, Contraction, and Transcription

Abstract: Calcium (Ca) is essential for excitation-contraction coupling. At the same time, Ca is of pivotal importance as a second messenger in cardiac signal transduction, where it regulates cardiac growth and function by activation of kinases and phosphatases, ultimately driving transcriptional responses and feeding back on Ca handling proteins, a phenomenon termed excitation-transcription coupling. Cardiac Ca homeostasis thus needs to be maintained via a delicate interplay of proteins to allow physiological function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 62 publications
0
10
0
3
Order By: Relevance
“…38 The TG mouse model offers a useful and clinically relevant model of hypertrophic cardiomyopathy, recapitulating a common clinical scenario where concentric, compensated hypertrophy ultimately decompensates with dilation and transition to arrhythmogenic failure associated with premature mortality. 5,21 The temporal pattern of altered Ca 2ϩ handling described in this study may be distinctive of an Ang II-G␣q pathology in the nonhypertensive setting. Cardiac Ang II levels increase in conditions of volume overload and in the postinfarct heart.…”
Section: Significance and Limitations Of The Modelmentioning
confidence: 67%
See 1 more Smart Citation
“…38 The TG mouse model offers a useful and clinically relevant model of hypertrophic cardiomyopathy, recapitulating a common clinical scenario where concentric, compensated hypertrophy ultimately decompensates with dilation and transition to arrhythmogenic failure associated with premature mortality. 5,21 The temporal pattern of altered Ca 2ϩ handling described in this study may be distinctive of an Ang II-G␣q pathology in the nonhypertensive setting. Cardiac Ang II levels increase in conditions of volume overload and in the postinfarct heart.…”
Section: Significance and Limitations Of The Modelmentioning
confidence: 67%
“…14 -16 This adaptive response depends on multiple factors, many of which are not yet known. [21][22][23][24] It is generally accepted, however, that altered function of RyRs and CICR, RyR-mediated Ca 2ϩ leak, deficient EC coupling, and/or changes in NCX and SERCA2 expression and activity can contribute to impaired myocyte contractility. 11,14,15,24 To gain insight into these complex interactions, we undertook a comprehensive investigation of cardiomyocyte Ca 2ϩ signaling at 2 different time points during the development of cardiac hypertrophy and failure.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivation of RyR2 may arise from activated protein kinase A by sympathetic neurons and increased levels of catecholamines, and subsequent hyperphosphorylation of RyR2 at Ser-2809 and dissociation of FKBP12.6 (Marx et al 2000) (but see Bers et al 2003;Seidler et al 2007;Yano et al 2008 ß-blockers prevent the hyperphosphorylation of RyR2 by protein kinase A, normalize channel function and improve cardiac function (Reiken et al 2001;Doi et al 2002). Heart failure can also be prevented by JTV519, which inhibits the dissociation of FKBP12.6 from RyR2; thereby stabilizing the channel, enhancing cooperativity among the subunits, and promoting coupled gating (Yano et al 2003;Wehrens et al 2005b).…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…This process, called "excitation-contraction" coupling, is now known to be a highly complex mechanism involving a number of tightly-coupled ion channels and transporters that regulate Ca 2+ entry from (and exit to) the extracellular environment as well as Ca 2+ release from (and uptake into) intracellular stores such as the sarcoplasmic reticulum (SR). This highly regulated process has long been known to involve L-type Ca 2+ channels and the Na + /Ca 2+ exchanger (NCX) in the plasma membrane, and ryanodine receptors (RyRs) and the sarco/endoplasmic reticulum Ca 2+ ATPase (SERCA) in the SR (reviewed by Bers, 2002;Seidler et al, 2007;Zhao et al, 2015). More recently, Ca 2+ release via inositol 1,4,5-trisphosphate receptors (IP 3 Rs) in the SR, and via the two pore channel 2 (TPC2) in lysosomes, Ca 2+ extrusion via the plasma membrane Ca 2+ ATPase (PMCA), Ca 2+ uptake into and release from mitochondria via a Ca 2+ uniporter and mitochondrial NCX, and modulation of Ca 2+ via sympathetic activation have been identified to play a role in normal heart function (Bers, 2002;Hund et al, 2008;Griffiths, 2009;Mohamed et al, 2010;Capel et al, 2015;Nita et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As well as regulating mature heart function via excitation-contraction coupling (Bers, 2002;Seidler et al, 2007;Greenstein and Winslow, 2011), Ca 2+ signaling has also been shown to play a role in heart development (Pucéat and Jaconi, 2005), via various different pathways and mechanisms, termed "excitation-transcription" coupling (Wu et al, 2006;Seidler et al, 2007). In zebrafish embryos, for example, a series of Ca 2+ transients were observed to be generated in the region of the developing heart; these transients were generated every 10-20 min and the Ca 2+ concentration was elevated 10-fold higher than the normal background level of Ca 2+ (Créton et al, 1998).…”
Section: Introductionmentioning
confidence: 99%